2007
DOI: 10.1021/es062009s
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and Chemical Factors in Clogging by Montmorillonite in Porous Media

Abstract: Clogging by colloid deposits is important in water treatment filters, groundwater aquifers, and petroleum reservoirs. The complexity of colloid deposition and deposit morphology preclude models based on first principles, so this study extends an empirical approach to quantify clogging using a simple, one-parameter model. Experiments were conducted with destabilized suspensions of sodiumand calcium-montmorillonite to quantify the hydrodynamic and chemical factors important in clogging. Greater clogging is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 36 publications
3
41
1
1
Order By: Relevance
“…Furthermore, the in situ FMBO impacted the characteristics of the particles and flocs, which also accounted for their strengthened attachment to the surfaces of the ripened sand. These results are in accordance with previous studies [33][34][35][36], suggesting that the particle deposition and the filter clogging depend on several factors such as hydrodynamic effects, solution chemistry, surface coatings, particle sizes and the interactions between suspended particles. Fabazi et al [37] investigated the role of polymers in improving floc strength for filtration, and found that the increased potential for floc growth can enhance the removal of small particles.…”
Section: Proposed Mechanisms Of the In Situ Fmbo Enhancing As Removalsupporting
confidence: 93%
“…Furthermore, the in situ FMBO impacted the characteristics of the particles and flocs, which also accounted for their strengthened attachment to the surfaces of the ripened sand. These results are in accordance with previous studies [33][34][35][36], suggesting that the particle deposition and the filter clogging depend on several factors such as hydrodynamic effects, solution chemistry, surface coatings, particle sizes and the interactions between suspended particles. Fabazi et al [37] investigated the role of polymers in improving floc strength for filtration, and found that the increased potential for floc growth can enhance the removal of small particles.…”
Section: Proposed Mechanisms Of the In Situ Fmbo Enhancing As Removalsupporting
confidence: 93%
“…Nine of these data sets, from seven of these studies, were previously analyzed by Mays and Hunt (2005) using a different permeability model. The other two data sets were reported by Mays and Hunt (2007). Each of these studies reported filtration tests where a constant concentration of suspended fines was pumped into an initially clean column of porous media under constant flow.…”
Section: Presentation Of Data and Resultsmentioning
confidence: 99%
“…Zengguang et al (2011) demonstrated from hydrodynamical simulations in a radial collecting system of a tailing dam that clogging occurred preferentially around the vertical shafts. Mays and Hunt (2007) showed that clogging increased with decreasing fluid speed. The main cause of precipitation is the adjustment in the partial pressure of carbon dioxide in keeping with the atmospheric pressure in the water.…”
Section: Recommendationsmentioning
confidence: 99%